Studi Ekstraksi Bijih Thorit dengan Metode Digesti Asam dan Pemisahan Thorium dari Logam Tanah Jarang dengan Metode Oksidasi-Presipitasi Selektif - Said, Moch Iqbal Nur; Anggraini, Mutia; Mubarok, Mohammad Zaki; Widana, Kurnia Setiawan (EKSPLORIUM, 2017)
Thorium (Th) is a radioactive metal that can be formed along with uranumand rare earth metals (REM). Minerals contain radioactive elements are monazite ((Ce,La,Y,U/Th)PO4), thorianite ((Th,U)O2), and thorite (ThSiO4). Mamuju Area is containing radioactive minerals, thorite is one of them. To separate REM from radioactive elements can be conducted by exctracting thorium from thorite ore by acid digestion method using sulphuric acid (H2SO4), followed by leaching and thorium recovery in the form of thorium hydroxide by chemical precipitation using ammonium hydroxide (NH4OH). The experimental results showed that the optimum conditions of acid digestion that give the highest Th extraction percentage on solid to liquid ratio are obtained at 1:2 (g/mL) in 60 minutes with extraction percentages of Th, iron (Fe) and REM are 82.47%, 80.08%, and 83.31% respectively. The highest thorium precipitation percentage, as much as 95.47% , was obtained at pH 4.5 on room temperature (26 ± 1°C). At higher temperature (70°C), a lower percentage of thorium precipitation is obtained, as much as 83.69%. Pre-oxidation by using H2O2 solution with two times stoichiometry for 1.5 hours at room temperature is increasing Fe precipitation percentage from 93.08% to 99.93%.